Optimalisasi Teknologi sebagai Media dalam Meningkatkan Pembelajaran Agama Islam di Era Digital - Tatta Herawati Daulae (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2024)
The existence of technology today provides excellent opportunities for the entire scope of human life. Activities are getting broader and more advanced, significantly to gain knowledge, more accessible, and more developed. This research was conducted in an effort to explan the urgency of technology and its role in the development of science. Technology and media are tools to facilitate human activities in various lines of life. Human life is currently in the digital era, which is a significant change in the entire order of life. The role of technology and media is vital in supporting human knowledge, namely helping to understand science and facilitate the search for knowledge. Thus, the role of technology as a medium for the development of science is enormous.